Standardisation of organic manures and effect of microbial inoculants on growth, yield and quality of kasthuri turmeric (curcuma aromatica salisb.) - Nirmalatha J D (Department of Plantation Crop and Spices, College of Agriculture, 2009)
The studies on the “Standardization of organic manures and effect of microbial inoculants on growth, yield and quality of kasthuri turmeric (Curcuma aromatica Salisb.)” were carried out at the Department of Plantation Crops and Spices, College of Agriculture, Vellayani, Thiruvananthapuram during 2006-2008.